Isolation and Pharmacological Characterization of α-Elapitoxin-Oh3a, a Long-Chain Post-Synaptic Neurotoxin From King Cobra (Ophiophagus hannah) Venom - Huynh, Tam M.; Silva, Anjana; Isbister, Geoffrey K.; Hodgson, Wayne C. (Frontiers in Pharmacology, 2022)
The King Cobra (Ophiophagus hannah) is the world’s largest venomous snake and has a widespread geographical distribution throughout Southeast Asia. Despite proteomic studies indicating the presence of postsynaptic neurotoxins in O. hannah venom, there are few pharmacological investigations of these toxins. We isolated and characterized α-elapitoxin-Oh3a (α-EPTX-Oh3a; 7938 Da), a long-chain postsynaptic neurotoxin, which constitutes 5% of O. hannah venom. α-EPTX-Oh3a (100-300 nM) caused concentration-dependent inhibition of indirect twitches and inhibited contractile responses of tissues to exogenous acetylcholine and carbachol, in the chick biventer cervicis nerve-muscle preparation. The prior incubation of tissues with Thai Red Cross Society King Cobra antivenom (1 ml/0.8 mg) prevented the in vitro neurotoxic effects of α-EPTX-Oh3a (100 nM). The addition of Thai Red Cross Society King Cobra antivenom (1 ml/0.8 mg), at the t90 time point partially reversed the in vitro neurotoxicity of α-EPTX-Oh3a (100 nM). Repeatedly washing the tissue did not allow significant recovery from the in vitro neurotoxic effects of α-EPTX-Oh3a (100 nM). α-EPTX-Oh3a demonstrated pseudo-irreversible antagonism of concentration-response curves to carbachol, with a pA2 of 8.99. De novo sequencing of α-EPTX-Oh3a showed a long-chain postsynaptic neurotoxin with 72 amino acids, sharing 100% sequence identity with Long neurotoxin OH-55. In conclusion, the antivenom is useful for reversing the clinically important long-chain α-neurotoxin-mediated neuromuscular paralysis.